Provincial and Territorial Government Contributions to the Development of Francophone Minority Communities: Assessment and Projections - Bourgeois, Daniel; Denis, Wilfrid; Dennie, Donald; Johnson, Marc L. (Canadian Institute for Research on LInguistic Minorities, 2007)
For more than forty years, the governments of the nine provinces and three northern territories that are majority Anglophone have been striving to promote the language and culture of their Francophone minority and thereby contribute to its development. Indeed, despite the importance of the federal government contribution, sectors such as education, health, and social and municipal services that are areas of exclusive provincial and territorial jurisdiction contribute to the vitality of Francophone communities. The lack of literature on provincial and territorial action in the area of official languages might lead one to think that such action is rare, or even non-existent, or that it is aimed at inhibiting the development of Francophone communities. It is nothing of the sort. Compilation and analysis of provincial and territorial actions in the area of official languages were thus required. It was necessary first to identify the nature of these actions and compile a list of them, and second to assess them critically. We then proposed a few immediate and long-term projections. The research covered nine sectors of activity: 1) public communications and services, 2) early childhood development, 3) health and well-being, 4) justice, 5) arts and culture, 6) economic development, 7) target groups (youth, seniors, and women), 8) immigration and 9) municipalities. The section on Health and Well-being discuss 6 themes: a) Legislation and Case Law; b) Policy; c) Programs and Services; d) Publications and Other Documents; e) Financial Support and Institutionalization; f) Training.
Research report prepared on behalf of the Ministerial Conference on the Canadian Francophonie

Qui sont les étudiantes du programme de formation francophone d’infirmières praticiennes? - Caty, Suzanne; Michel, Isabelle; Pong, Raymond; Stewart, Dianne (Ref;ets, 2007)

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)